Separate evaluation of interface and oxide hole traps in SiO2/GaN MOS structures with below- and above-gap light excitation - Takuma Kobayashi; Kazuki Tomigahara; Mikito Nozaki; Takayoshi Shimura; Heiji Watanabe (Applied Physics Express, 2023)
Understanding the traps in metal-oxide-semiconductor (MOS) structures is crucial in the fabrication of MOS transistors with high performance and reliability. In this study, we evaluated the hole traps in SiO _2 /GaN MOS structures through photo-assisted capacitance-voltage measurements. Below- and above-gap light was used to distinguish between the contributions of fast interface and slow oxide hole traps. While annealing in oxygen is effective in reducing the oxide hole traps, a high density of hole traps exceeding 10 ^12 cm ^−2 eV ^−1 remains at the interface. Although these traps are donor-type and thus hidden in n-type MOS structures, they could impair the switching performance of GaN MOS transistors.